Adaptation of New Superior Varieties and Planting Systems on Growth and Production of Rice - Sution Sution; Serom Serom (Agros Journal of Agriculture Science, 2017)
This study aims to obtain adaptive varieties with appropriate cropping systems on growth and yield of wetland rice. Design used is Split Plit Design, varieties as main plot and planting system as subplot. Varieties consist of two levels, namely Inpara 2 and Inpari 30. Plant spacing consists of five levels, namely tile planting system, legowo 2:1(20-40)x10cm, legowo 2:1(20-50)x10cm, legowo 2:1(25-40)x12.5cm, and legowo 2:1(25-50)x12.5cm. There are 10 treatment combinations, repeated three times, in total there are 30 plot experiments. Results: Inpara 2 and Inpari 30 varieties there were no significant differences to plant height, number of panicles per hill, panicle length, number of grain per panicle, percentage of unhulled grain, number of grains per panicle, and weight of 1000 grains. Legowo 2:1(20-40)x12.5cm has significant effect on plant height, 81.28 and 80.39cm respectively. Treatment  legowo 2:1(25-50)x12,5cm, (25-40)x12,5cm, and (25-40)x10cm systems had highest number of panicles per hill: 12.94;12,44;and 11.72 panicles. Grain per panicle, percentage of unhulled grain, and grains number per panicle have same pattern, that is highest with 2:1 legowo system (20-40)x10cm, highest 1000 grain of legowo 2:1 planting system (20-40)x10cm and (25-50)x12.5cm respectively 24.51 and 25.35 g. Yield of Inpara 2 and Inpari 30 varieties with legowo 2:1 system is significantly different from tile planting system. Key-words: legowo, adaptation, rice paddy